Innovation in Family Business and Cooperation: A Literature Review - Soler-Porta, Mariano; Padilla-Meléndez, Antonio; Rodríguez-Díaz, Beatriz (European Journal of Family Business, 2019)
In this paper, after some clarifications about the definition and characteristics of Family Business (FB), a literature review on innovation and cooperation in FB has been conducted. As a consequence, a research gap regarding how FB develops innovation when cooperating with external factors has been identified. In particular, specific characteristics of FB have been analysed regarding innovation and cooperation, such as longer-term vision, risk aversion, and relatively lack of professionalism of FB workers.